Axial meso-scale modeling of gas-liquid-solid fluidized beds. (16th March 2019) - Ma, Yongli; Liu, Mingyan; Zhang, Yuan
Graphical abstract: Highlights: Axial meso-scale model of gas-liquid-solid fluidization is established. Momentum exchanges are quantified by bubble and particle accelerations. Model can predict the axial distributions of all the flow parameters. Model can predict the variation of transition with operation conditions. Abstract: The meso-scale theory, based on the energy minimization multi-scale principle, has recently inspired the accurate modeling of the multi-phase flow. In this study, an axial meso-scale flow model for the gas-liquid-solid fluidized bed is established and verified by the literature models and data. Compared with the reported axial models, this model predicts the axial distribution of all three-phase hydrodynamic parameters with fewer empirical corrections. Predictions of the present model show that the operation conditions and physical properties of solid particles obviously affect the flow behaviors of phases, such as the slip velocity, entrainment of solid particles, wake shedding parameters. Solid particles entrained by bubble wake determine the formation of axial distribution in the gas-liquid-solid fluidized bed. Region with the axial structure is the transition section, length of which depends on the entrainment of solid particles. Furthermore, behaviors of the gas bubbles and the solid particles are mutually influential.